Study on the properties of sinusoidal micro-textured ball end milling cutter for milling titanium alloy - Li, Qinghua (Strojniški vestnik, 2024)
To improve the cutting performance when cutting hard alloys and achieve reasonable optimization of micro-texture parameters, this paper proposes a sinusoidal micro-textured tool, with four parameters set as micro-textured spacing, period, width, and amplitude. Establish three-dimensional models of non-micro-textured and micro-textured milling tools and simulate the milling process using finite element simulation. Study the effects of milling force and milling temperature on tool performance. Prepare micro-textured milling tools for orthogonal experiments, analyse the effects of milling force and the surface roughness of a titanium alloy workpiece, and study the impact of different micro-textured parameters on milling tool performance. Obtain the parameters that have the greatest impact on milling tool performance, and then use genetic algorithm to optimize three sets of parameter combinations. Use the optimized parameters to prepare milling tools for comparative experiments, and then determine the optimal parameter combination. The research results indicate that micro-textured tools can effectively improve the milling performance of the tool, and the spacing between sinusoidal micro-textures has the greatest effect on improving the milling performance of the tool. When the period of sinusoidal micro-texture is 2.87 and the amplitude is 25.13 µm, width is 79.89 µm, and spacing is 134.54 µm, the milling performance of the tool is optimal.
Keywords: hrapavost površine; milling force; milling temperature; milling tools; obdelava z rezkanjem; optimizacija parametrov; parameter optimization; rezkalna orodja; sile pri rezkanju; sinusoidal micro-texture; sinusoidna mikrotekstura; surface roughness; temperature pri rezkanju; titanium alloy; titanova zlitina